2022
DOI: 10.1038/s41467-021-27822-3
|View full text |Cite
|
Sign up to set email alerts
|

Design principles for site-selective hydroxylation by a Rieske oxygenase

Abstract: Rieske oxygenases exploit the reactivity of iron to perform chemically challenging C–H bond functionalization reactions. Thus far, only a handful of Rieske oxygenases have been structurally characterized and remarkably little information exists regarding how these enzymes use a common architecture and set of metallocenters to facilitate a diverse range of reactions. Herein, we detail how two Rieske oxygenases SxtT and GxtA use different protein regions to influence the site-selectivity of their catalyzed monoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(60 citation statements)
references
References 60 publications
0
60
0
Order By: Relevance
“…All three chiral centers in Chl a , b , and intermediates are labeled with a red asterisk and for the chemical structure, R = H or C 20 H 39 for chlorophyllide and chlorophyll pigments, respectively. This proposal for CAO is unlike that for other transformations that proceed through more than one monooxygenation reaction and require two Rieske oxygenases to be completed. This proposal is also unlike that needed to convert a methyl group into a formyl group in the catabolism of 4-toluene sulfonate, which requires both a Rieske oxygenase and dehydrogenase . (b) CAO has potential to be used as a tool for formylating the Chl scaffold to produce custom-tuned native and non-native pigments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All three chiral centers in Chl a , b , and intermediates are labeled with a red asterisk and for the chemical structure, R = H or C 20 H 39 for chlorophyllide and chlorophyll pigments, respectively. This proposal for CAO is unlike that for other transformations that proceed through more than one monooxygenation reaction and require two Rieske oxygenases to be completed. This proposal is also unlike that needed to convert a methyl group into a formyl group in the catabolism of 4-toluene sulfonate, which requires both a Rieske oxygenase and dehydrogenase . (b) CAO has potential to be used as a tool for formylating the Chl scaffold to produce custom-tuned native and non-native pigments.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in other biosynthetic pathways where two oxygenation reactions are required, multiple proteins work together (Figure a). The two required oxygenations on the saxitoxin scaffold are made by the Rieske oxygenases SxtT and GxtA (Figure a). Likewise, two Rieske oxygenases, NdmA and NdmB, catalyze iterative oxidative demethylation reactions in caffeine degradation (Figure a) . The Rieske oxygenase 4-toluenesulfonate methyl monooxygenase (TsaM) also catalyzes a methyl- to formyl-group transformation to convert 4-tolunesulfonate into 4-sulfobenzoate .…”
Section: Introductionmentioning
confidence: 99%
“…Based on sequence alignments, this residue appears to be a hallmark of quaternary-ammonium-substrate-oxidizing Rieske oxygenases [ 39 ]. Along these lines, the α 3 Rieske oxygenases SxtT and GxtA, which catalyze monooxygenation reactions at the C12 and C11 positions of a tricyclic saxitoxin scaffold, respectively, use two active site residues to hold the substrate such that the correct carbon-atom is positioned for hydroxylation ( Figure 2f ) [ 37 , 38 , 50 ]. Two important structural studies on CARDO have revealed that mutations in the active site can change the openness of the substrate-binding pocket, the orientation in which the substrate binds, and the outcome of the hydroxylation event ( Figure 2g ) [ 36 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen activation and substrate oxidation occur at the mononuclear iron site with the reduced Rieske cluster [Fe­(II)-Fe­(III)], providing an essential electron for the process. Despite the many fundamental similarities of the RO enzymes, considerable specificity in substrate selection, reaction type, and regiospecificity is observed for individual family members. X-ray crystal structures of ROs that catalyze a range of reaction types fail to distinguish a basis for this specificity in the structural regions encompassing the Rieske cluster, the residues between the metal centers, and mononuclear iron ligation, which are remarkably conserved. ,,,, Progress has been made in understanding the key features of the active site surrounding the mononuclear iron that orient the substrate and provide a level of regiospecificity. ,,, However, there is currently little insight into whether the various reactivities require different types of activated oxygen species or how such divergent species might evolve from a highly conserved metal center.…”
Section: Introductionmentioning
confidence: 99%